ARTIFICIAL INTELLIGENCE - Khodjarakhmanova Nazira; Izbosarov Boburjon Bakhriddinovich (Galaxy International Interdisciplinary Research Journal, 2022)
Artificial intelligence is a specific part of digitization that typically involves robots or computers performing tasks that the human mind can perform. Examples include computer systems, like the online translators we use to translate from one language to another, or which show the shortest route when we use a car and provide information about how long it will take us to get to our destination, etc. In addition, "online calculators", which are very popular among young learners today, are systems that can solve existing mathematical problems and examples according to a certain algorithm. In this article both good sides and bad sides of artificial intelligence is discussed below